Tobacco Taxation Influences the Smoking Habits of Adult Smokers Attending Smoking Cessation Clinic in Saudi Arabia - Najeeb Saud S. Altowiher; Rami Bustami; Ali M. Alwadey; Mansour Alqahtani (Frontiers Media S.A., 2022)
ObjectivesTo determine whether the increased tobacco price due to tax implementation on tobacco products (including cigarettes) has a significant effect on smoking cessation among Saudi Arabian adult smokers.MethodsAn interviewer-administered questionnaire was used to obtain data from adult Saudi smokers and recent quitters attending smoking cessation clinics between January 2018 and September 2019. The responses of the participants were summarized and analyzed.ResultsIn total, 660 participants were interviewed, of which 98% were men who resided in the western region (33%). Taxation had no effect on smoking in 387 participants [58.6%; 95% confidence interval (CI): 54.9, 62.4], some effect in 220 participants (33.3%; 95% CI: 29.7, 36.9), and a substantial effect in 50 participants (7.6%; 95% CI: 5.6, 9.6). Strategies adopted to cope with the tax implementation included cutting down on the number of cigarettes smoked (302; 45.8%), changing to a cheaper brand of cigarette (151; 22.9%), purchasing in bulk (105; 15.9%), attempting to quit (453; 68.6%), and doing nothing (108; 16.4%). The rate of quitting smoking after attending the clinic was 20.7% (95% CI: 17.7, 23.9). Occupation (P = 0.003), education (P = 0.03), and current smoking habit (P = 0.07) were significantly associated with the impact of tobacco taxation. The strategies adopted in response to tax implementation on cigarettes were significantly associated with occupation (χ2 = 30, degrees of freedom = 12, P < 0.001).ConclusionsTobacco taxation influenced 40% of the participants. Their attempts to opt for alternatives should be recognized in evaluating policies to reduce adverse health impacts caused by tobacco abuse.